Sistem Penentuan Keputusan Seleksi Pemilihan Asisten Dosen Sistem Informasi Dengan Penerapan Metode TOPSIS - Renny Puspita Sari; Muhammad Aidil Rifaldi (Universitas Budi Darma, 2022)
The selected lecturer assistant can help the lecturer as a liaison with students so that the lecturer assistant can affect the quality of student learning outcomes. It's just that the acceptance of teaching assistants that were previously less effective and efficient because they still use manual rules and procedures, so they can spend time in their determination, besides that the assessment is still subjective or still looks at the closest family to one candidate in the acceptance of teaching assistants and there are no requirements The right specialty in determining lecturer assistants, causing problems, namely difficulties in determining a suitable lecturer assistant and having skills in his field, In making the wrong decision it results in distrust of the accepted lecturer assistant so that it can have an impact on decreasing students' understanding and skills of the subject. Therefore, a system is needed to solve a problem by providing decision making, so that it can help decision makers in determining the graduation of the right lecturer assistant. The TOPSIS method is applied by the author in this journal, because the TOPSIS method is able to overcome MADM problems so it is very practical in completing a decision, besides that the alternative TOPSIS method selected is obtained from the calculation process and after that ranking is carried out, so that from the process the best alternative is obtained from criteria that have been determined, so that it can be used as a solution in decision making. Because the system takes the value from the best criteria, the accuracy obtained in this system exceeds 90%.